0460 Smoking adjusted occupational risk of bladder cancer using proxy smoking from lung cancer in nordic males. (21st August 2017) - Hadkhale, Kishor; Martinsen, Jan Ivar; Weiderpass, Elisabete; Kjaerheim, Kristina; Lynge, Elsebeth; Sparen, Pär; Tryggvadottir, Laufey; Pukkala, Eero
Abstract : Withdrawn at the author's request